Ferroelastic Domain Switching and Time‐Resolved Negative Capacitance in Polar‐Axis‐Oriented Hf 0.5 Zr 0.5 O 2 Grown by Atomic Layer Epitaxy - Jiang, Yu‐Sen; Lin, Wei‐En; Shiojiri, Makoto; Yin, Yu‐Tung; Su, Yu‐Cheng; Nien, Chih‐Hung; Hsu, Chen‐Feng; Hou, Vincent Duen‐Huei; Chang, Chih‐Sheng; Radu, Iuliana; Chen, Miin‐Jang (Small (Weinheim an der Bergstrasse, Germany), 2025)
Ferroelectric properties of Hf 0.5 Zr 0.5 O 2 are strongly correlated with its crystallographic orientation, with the [001] direction serving as the polar axis. However, the epitaxial growth of highly polar‐axis‐oriented Hf 0.5 Zr 0.5 O 2 layers with pronounced ferroelectricity is rarely reported. Here epitaxial (001)‐oriented Hf 0.5 Zr 0.5 O 2 thin films grown by atomic layer epitaxy (ALE) is demonstrated, which achieve a state‐of‐the‐art ferroelectric polarization up to 78.9 µC cm −2 . The epitaxial Hf 0.5 Zr 0.5 O 2 layer experiences a lattice reorientation from (010) to (001) during the wake‐up process, as evidenced by plane‐view precession electron diffraction. Accordingly, a two‐step, 90° ferroelastic domain switching model is proposed to elucidate multiple polarization switching. Furthermore, the observed polarization switching dynamics closely match with the time‐resolved negative capacitance, which is quantified as an equivalent high dielectric constant of −170. This study highlights the capability of ALE to precisely control the crystallographic orientation of Hf 0.5 Zr 0.5 O 2 thin films, providing deep insights into fundamental ferroelectric mechanisms.